(untitled) (Bangladesh Journal of Animal Science, 2013)
The present study was conducted to investigate the effect of age on slaughterhouse by-products and their chemical composition of indigenous cattle of Bangladesh. Live weight, warm carcass weight and dressing percentage of different age group (T1= 0 Tooth, T2= 2 Teeths, T3= 4 Teeths, T4= 6 Teeths and T5= 8 Teeths) of indigenous cattle were estimated. Average live weight and warm carcass weight of indigenous cattle was 167.64±79.93 kg and 84.83±47.88 kg, respectively on which age has significant effect. The average dressing percentage of indigenous cattle was 48.99±4.84. The average weight (kg) of inedible by-products eg. blood, hide, tail, scrotum, penis, cannon, horn, ear and tail was 6.35±0.69, 14.02±1.66, 0.34±0.03, 0.27±0.02, 0.28±0.03, 2.74±0.22, 0.33±0.04 and 0.17±0.02, respectively on which age has significant effect. The average weight (kg) of edible by-products eg. liver, heart, kidney, lung, brain, spleen, empty stomach, empty intestine, head and tongue was 2.40±0.22, 0.55±0.06, 0.35±0.04, 1.43±0.14, 0.33±0.01, 0.46±0.04, 6.32±0.74, 4.77±0.52, 8.21±0.78 and 0.48±0.04, respectively on which age has significant effect. The chemical composition of edible by-products was more or less similar to the main products of meat industry. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15784 Bang. J. Anim. Sci. 2013. 42 (1): 62-66